2009
DOI: 10.1021/jp8102518
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Properties of C60 Colloids Suspended in Water with Triton X-100 Surfactant: Excited-State Properties with Femtosecond Resolution

Abstract: We examine the photophysics of a colloidal suspension of C 60 particles in a micellar solution of Triton X-100 and water, prepared via a new synthesis which allows high-concentration suspensions. The particle sizes are characterized by transmission electron microscopy and dynamic light scattering and found to be somewhat polydisperse in the range of 10-100 nm. The suspension is characterized optically by UV-vis spectroscopy, femtosecond transient absorption spectroscopy, laser flash photolysis, and z-scan. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
12
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 88 publications
4
12
0
3
Order By: Relevance
“…In addition, the triplet state lifetime of C 60 was 343 ns in the TPP/C 60 mixture, similar to the reported value 330 ns for C 60 alone [19,20]. This suggests weak or no interaction between TPP and C 60 in the mixture.…”
Section: Nanosecond Transient Absorptionsupporting
confidence: 85%
“…In addition, the triplet state lifetime of C 60 was 343 ns in the TPP/C 60 mixture, similar to the reported value 330 ns for C 60 alone [19,20]. This suggests weak or no interaction between TPP and C 60 in the mixture.…”
Section: Nanosecond Transient Absorptionsupporting
confidence: 85%
“…This is in stark contrast to other nanomaterials such as carbon nanotubes 32 or C 60 fullerenes, 33 where anionic surfactants generally lead to strong exciton quenching. This robustness highlights the viability of surfactant-assisted liquid processing (exfoliation, deposition, printing, etc) of MoS 2 and other semiconducting TMDs.…”
Section: Resultsmentioning
confidence: 71%
“…It has been reported that defects inside solids can easily act as quenchers or trap sites. 14,20 It is notable that the reported intrinsic (monomeric) decay time of the singlet excited state of C 60 thin films is about 100 ps, 24 which is approximately 10 times that of nC 60 in water. It could be considered that the singlet excited state is quenched efficiently at the nanoparticle/ water interface.…”
mentioning
confidence: 99%
“…20,24,25 Recently, Clements et al reported similar results of transient absorption experiments on nC 60 dispersed in a micellar solution of Triton X-100 and water. 14 They attributed the shortened lifetime to singlet annihilation; however, they did not examine the excitation intensity dependence.…”
mentioning
confidence: 99%
See 1 more Smart Citation